Did lynchings occur during witch hunts in Poland between the 16th and 18 th centuries? - Wijaczka, Jacek (Studia Iuridica Toruniensia, 2023)
In his synthesis Witch Hunts in Poland in the 17th and 18th century Bohdan Baranowski formulated a thesis that about 5,000 women accused of witchcraft lost their lives as a result of lynching executions which occurred primarily in rural areas. However, he did not provide specific source examples to support this thesis. The hypothesis entered the source literature nonetheless, and subsequent historians considered it a certainty. The analysis of the subject related the literature to date and the archival research, including the investigation of trials held in Gniezno in 1690, shows that lynchings hardly ever occurred in Poland. There were only two such cases, the first in 1720 in the town of Krasiłów, the 308Jacek Wijaczka second in the village of Osowo near Tuchola in 1779. The ‘trial’ con- ducted in Czerniewo in 1727, however, can be considered as an extra- judicial lynching; the perpetrators and adjudicators were consequently punished. Bohdan Baranowski’s 1952 thesis was therefore rather unsubstantiated.